POLA USAHA DAN PENDAPATAN RUMAH TANGGA PETANI PADA BERBAGAI TIPOLOGI LAHAN RAWA LEBAK - Nasir Nasir; Imron Zahri; Andy Mulyana; Yunita Yunita (Jurnal Manajemen & Agribisnis, 2015)
The study aim to 1) Describing of business pattern developed farmer households in various typologies of lowland swamp land, and 2) Analyzing household income of farmers in various businesses developed in lowland swamp land. The sampling method used is a simple random sample with a total of  responden  as many as 222 farmers. The study used a survey method. The results showed that the business pattern of households at shallow swampy, ie: Horticulture: annual fruit, Livestock: chickens and goats, trade, household industry, transport services, Rice, fishing, horticulture: vegetables and fruits a season and crops: cassava and peanuts, Labour, fish farming. The business pattern of households at middle swamp, ie: horticulture: annual fruit, Livestock: ducks, trade, household industry, transport services, rice, fishing, horticulture: vegetables and fruits a season, Labor, fish farming. The business pattern of households at deep swampy, ie: Horticulture: annual fruit, Livestock: duck and buffalo, trade, household industry, transport services, rice, fishing, horticulture: vegetables and fruits a season, Labor, fishing, fish farming. Household income in each of the  swampy land, ie: household income  the shallow swampy amounted Rp19.525.400/year.  The household income  the middle swampy amounted Rp20.212.000/year.  The household income the deep swampy amounted Rp18.248.000/yearKeywords: pattern of business, income, household, lebak, surveyABSTRAKTujuan penelitian ini 1) mendeskripsikan pola usaha yang dikembangkan rumah tangga petani pada berbagai tipologi lahan rawa lebak, dan 2) menghitung pendapatan rumah tangga petani pada berbagai pola usaha yang dikembangkan pada lahan rawa lebak. Metode penarikan contoh yang digunakan adalah sampel acak sederhana (random sampling) dengan jumlah total sebanyak 222 orang petani. Metode penelitian yang digunakan adalah metode survei. Hasil penelitian menunjukan bahwa pola usaha yang dikembangkan petani lahan rawa lebak pematang adalah: hortikultura:buah-buahan tahunan, Ternak: ayam dan kambing, dagang, industri rumah tangga, jasa angkutan, padi, penangkapan ikan, hortikultura: sayuran dan buah-buahan semusim dan palawija: ubi kayu dan kacang tanah, Buruh, budi daya ikan. Pola lebak tengahan: hortikultura:buah-buahan tahunan, Ternak: itik, dagang, industri rumah tangga, jasa angkutan, padi, penangkapan ikan, hortikultura: sayuran dan buah-buahan semusim, Buruh, budi daya ikan.  Pola usaha rumah tangga pada lebak dalam: hortikultura:buah-buahan tahunan, Ternak: itik dan kerbau, dagang, industri rumah tangga, jasa angkutan, padi, penangkapan ikan, hortikultura: sayuran dan buah-buahan semusim, Buruh, penangkapan ikan, budi daya ikan. Pendapatan rumah tangga yang mengusahakan lebak, yaitu lebak tengahan: Rp20.212.000/rumah tangga/tahun, lebak pematang Rp19.525.400/rumah tangga/tahun dan lebak dalam Rp18.248.000/rumah tangga/tahun. Kata kunci: pola usaha, pendapatan, rumah tangga, lebak, survei